Evaluation of Rock Fall Risk in Kilis (Turkey) City by Using GIS and Remote Sensing - ÇELİK, Mehmet Ali; GÜLERSOY , Ali Ekber (International Journal of Computational and Experimental Science and Engineering, 2017)
Rapid increase in population results in rapid but not planned growth of residential areas and subsequently residential areas shift from their initial position to various risk including regions. Natural disasters are inevitable once the cities are not properly planned in countries like Turkey characterized with geological, geomorphological and climatological diversity. It is worthy to note that disaster risk profile in Turkey is very high according to the natural disasters historical data. Of the natural disasters, rock fall is one of threats for Turkey. The definition of rock fall may be simplified as quantities of rock falling freely from a cliff face. In order to monitor the possible and potential rock fall risks, base maps of the study area (Kilis, Turkey) was obtained using geographical information system (GIS) techniques and remote sensing data. The base maps were produced considering the parameters affecting the rock fall. Finally, rock fall risk map for the region was obtained by overlapping the maps using GIS techniques. The results exhibit that 3.22 % of the regions has high potential risk of rock fall. Based on the results, local decision makers concerned with urbanization plans should consider the regions with high rock fall risks. Otherwise, the loss of life and property is inevitable as consequences of natural disasters